(untitled) (Texas Journal of Engineering and Technology, 2025)
Oil-injected screw compressors are widely used in compressed-air, refrigeration and gas-handling plants because they deliver steady flow from a compact rotating machine. In service, vibration at rotor, bearing, gear and support interfaces can shorten bearing life, increase leakage, raise noise and cause unplanned shutdown. This study examines the vibration behaviour of an Ingersoll Rand R110i oil-injected screw compressor by combining five-month field measurements, finite element modal interpretation, a simplified flow-path assessment and component material screening. Vibration was measured at the compressor and motor drive-end and non-drive-end locations in the horizontal, vertical and axial directions using an SKF Microlog analyser in RMS velocity mode. The highest measured value was 31.75 mm/s at the motor nondrive-end vertical point. Compressor-side readings were much lower and more stable, showing that the dominant field problem was concentrated at the motor support path rather than across the compressor body. A SolidWorks-based assembly model was used to compare materials for the rotors, casing, bearings, gears and damping elements. The selection process considered density, stiffness, fatigue strength, corrosion or wear resistance, damping capacity, manufacturability and cost. The selected configuration was Ti-6Al-4V for the rotors, ASTM A48 Class 35 cast iron for the casing, silicon nitride for the bearings, AISI 8620 casehardened steel for the gears and polyurethane for the damping elements. Under the linear-elastic and simplified-support assumptions used in the model, the optimized assembly gave a simulated response velocity of 3.1496 × 10−4 mm/s and a maximum Von Mises stress of 379.6 psi. The velocity value is a numerical response indicator from the model, not a measured operating vibration value. The simplified flow assessment showed gradual pressure development across the rotor-casing path, with no pronounced recirculation pocket or velocity bottleneck. The study recommends two actions: immediate correction of the motor non-drive-end support condition and later prototype validation of the selected material configuration